2017
DOI: 10.3390/rs9090954
|View full text |Cite
|
Sign up to set email alerts
|

Active Nonlinear Acoustic Sensing of an Object with Sum or Difference Frequency Fields

Abstract: A number of nonlinear acoustic sensing methods exist or are being developed for diverse areas ranging from oceanic sensing of ecosystems, gas bubbles, and submerged objects to medical sensing of the human body. Our approach is to use primary frequency incident waves to generate second order nonlinear sum or difference frequency fields that carry information about an object to be sensed. Here we show that in general nonlinear sensing of an object, many complicated and potentially unexpected mechanisms can lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Refs. [11,23] studied the generation of f s from two primary signals only (which can be useful due to its high spatial resolution and accuracy), but here we also analyzed its maximization. The results of this work showed that we could obtain much higher amplitudes of f s by slightly reducing one of the primary frequencies (see Section 3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Refs. [11,23] studied the generation of f s from two primary signals only (which can be useful due to its high spatial resolution and accuracy), but here we also analyzed its maximization. The results of this work showed that we could obtain much higher amplitudes of f s by slightly reducing one of the primary frequencies (see Section 3).…”
Section: Methodsmentioning
confidence: 99%
“…These techniques rely on the detection of transmitted or reflected ultrasonic waves. They use the signals emitted from the source (primary frequencies) during the entire process [6], which falls under the linear theory valid for infinitesimal pressure amplitudes, or consider combinations of the source signals such as harmonics, difference frequencies, sum frequencies, subharmonics [7][8][9][10][11], which falls under the nonlinear theory (at least second-order terms) valid for finite pressure amplitudes. The benefits of the signal produced at the difference frequency by parametric arrays stand in its low attenuation and high directivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide area scattering strength images were produced by beamforming, matched filtering and charting the received OAWRS returns and then correcting for transmission loss (Andrews, Gong, & Ratilal, ; Gong et al., ; Jagannathan et al., ; Makris et al., , ; Naftali & Makris, ). Linear frequency modulated (LFM) source waveform transmissions of 50 Hz bandwidth and 1‐s duration centred at 955 Hz were used for the OAWRS cod measurements presented, which are above but within a decade of the expected swimbladder scattering resonance frequencies (Blaxter & Batty, ; Gong et al., ; Jagannathan et al., ; Jain et al., ; Love, ; Løvik & Hovem, ; Zhang, Liu, Ratilal, Cho, & Makris, ) of spawning cod in this region. Scattering strength was converted to areal population density by calibration with local in situ measurements of areal population density obtained from vertical echo sounding.…”
Section: Methodsmentioning
confidence: 99%
“…For inhomogeneities with zero forward direction velocity, the Doppler spread term and the amplification factor vanishes, and so the modal field-temporal-covariance coefficient reduces to Eqs. (5) and (8) of ref. 26 .…”
Section: Analytic Expressions For the Mean And Temporal Correlation Omentioning
confidence: 99%